Glue, the Trainspotting novels and transition from working-class solidarity to neoliberal entrepreneurship - Amaury Garcia Santos Neto (Ilha do Desterro)
This article discusses some of Irvine Welsh’s novels considering the period of transition from industrial to post-industrial society. We focus on the effects of this shift on fictional characters who originate from the working classes in Edinburgh, as represented in Welsh’s Glue (2001) and the Trainspotting Novels. As such works cover the period from the early 1970’s to the late 2010’s, Welsh evidences the move from the traditional working-class ethos, typified by Union solidarity, to the neoliberal culture of entrepreneurship and its related negative aspects. We propose to discuss how Welsh depicts neoliberal practices either rendering workers redundant for the new circumstances or creating new ways to exploit labour.